2002
DOI: 10.1515/bc.2002.083
|View full text |Cite
|
Sign up to set email alerts
|

Altered Storage of Proteases in Mast Cells from Mice Lacking Heparin: A Possible Role for Heparin Carboxypeptidase A Processing

Abstract: Heparin-deficient mice, generated by gene targeting of N-deacetylase/N-sulfotransferase-2 (NDST-2), display severe mast cell defects, including an absence of stored mast cell proteases. However, the mechanism behind these observations is not clear. Here we show that NDST-2+/+ bone marrow-derived mast cells cultured in the presence of IL-3 synthesise, in addition to highly sulphated chondroitin sulphate (CS), small amounts of equally highly sulphated heparin-like polysaccharide. The corresponding NDST-2-/- cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…C, effect of SG on granzyme B activity. Extracts were prepared from non-stimulated spleen cells (empty symbols) and from ConA-stimulated (3 days) spleen-derived CTLs predominantly highly sulfated GAGs of heparin type ([IdoUA-GlcNAc] n carbohydrate backbone) (36), whereas bone marrow-derived mast cells synthesize GAG chains of equally high charge density albeit of chondroitin sulfate type ([GlcUA-GalNAc] n carbohydrate backbone) (37). In contrast, SG produced by macrophages (38) and NK cells (17) contain chondroitin sulfate chains of much lower charge density.…”
Section: Discussionmentioning
confidence: 99%
“…C, effect of SG on granzyme B activity. Extracts were prepared from non-stimulated spleen cells (empty symbols) and from ConA-stimulated (3 days) spleen-derived CTLs predominantly highly sulfated GAGs of heparin type ([IdoUA-GlcNAc] n carbohydrate backbone) (36), whereas bone marrow-derived mast cells synthesize GAG chains of equally high charge density albeit of chondroitin sulfate type ([GlcUA-GalNAc] n carbohydrate backbone) (37). In contrast, SG produced by macrophages (38) and NK cells (17) contain chondroitin sulfate chains of much lower charge density.…”
Section: Discussionmentioning
confidence: 99%
“…In line with such an explanation, it was recently shown that mast cell carboxypeptidase A expressed by bone marrow-derived mast cells is strictly dependent on heparin glycosaminoglycan for storage and processing, whereas mast cell tryptase can be stored and processed also in cells lacking heparin but containing chondroitin sulfate of equal charge density [35].…”
Section: Discussionmentioning
confidence: 87%
“…As can be seen in Table 1, PMA treatment resulted in a 50-80% increase in total proteoglycan synthesis. Further, treatment of the cells with HX-xyl, both in the presence or absence of PMA, resulted in a marked ( threefold) increase in the synthesis of 35 S-labelled macromolecules (Table 1). After HX-xyl treatment, the major part of the 35 S-labelled macromolecules expressed was recovered in the culture medium, regardless if PMA was present or not (Table 1).…”
Section: Xyloside and Proteoglycan Expressionmentioning
confidence: 97%
See 2 more Smart Citations